Answer:
B -6x+35=-6x+35
Explanation:
Let's analyze the options:
A ........................
- 6x+35=-6x-35
- 6x + 6x = -35 - 35
- 12x = - 70
- x = -70/12
This one has one solution
B ........................
- -6x+35=-6x+35
- - 6x + 6x = 35 -35
- 0 = 0
This one has infinitely many solutions as results in true equation for any value of x
C ........................
- 6x+35=-6x+35
- 6x + 6x = 35 -35
- 12x = 0
- x = 0
This one has one solution
D ........................
- -6x+35=-6x-35
- -6x +6x = - 35 - 35
- 0 = -70
This one has no solutions as results in false equation for any value of x